East-West dichotomy and political conflict in Ukraine - Was Huntington right? - Karácsonyi, Dávid; Kocsis, Károly; Kovály, Katalin; Molnár, József; Póti, László (Hungarian Geographical Bulletin, 2014)
In his work the Clash of Civilizations S. P. Huntington classified Ukraine as a "cleft country". In our view, the current discord in Ukraine is rooted in the political divisions that have frequently characterised the post-communist countries. In Ukraine, owing to a history of divergent socio-economic development in the various regions, these divisions are strongly regional. The dichotomic socio-economic framework reflects not only ethnic and religious differences but also such factors as urbanisation, economic development, and even natural elements. The resulting political divide in Ukraine may be traced to the dichotomy of its national identity. The dividing line is between east and west, urban and rural, and Russian-speaking and Ukrainian-speaking Ukraine. Politically, it is between "Maidan-Ukraine" and "Anti-Maidan-Ukraine". The divide runs along the Uman'-Kharkiv line between the forest zone and the steppe. In the 18 th century the steppe - which had once been a corridor for the nomadic peoples - became a frontier territory for the Ukrainians and then for Tsarist Russia. The Russian ties of cities in the region were further strengthened by industrialisation in the 19th and 20th centuries and by Russification in the Soviet era. The Soviet-made famine (Holodomor) and the events of World War II (the actions of the UPA) heightened Ukraine's political dichotomy. Since independence Ukraine's political elite has failed to address the problem in an adequate manner. The recent escalation of the conflict is due to a lack of political cohesion in the young state and the gravitational effect of the major powers rather than primarily to some kind of civilizational difference. By accentuating Ukraine's economic and financial difficulties, the global crisis has made the country even more vulnerable.